Outbreak of Tinea capitis by Trichophyton tonsurans and Microsporum canis in Niterói, RJ, Brazil - Towersey, Loan; Hay, Roderick James; Monteiro, Maria Helena; Lago, Márcio Brito; Martins, Eunice de Castro Soares; Estrella, Rogério Ribeiro (Revista do Instituto de Medicina Tropical de São Paulo, 1992)
18 girls from an orphanage (Orfanato Santo Antônio) in Niterói presented tinea capitis due to Trichophyton tonsurans (15 cases - 83.3%) and Microsporum canis (3 cases - 26.7%). Comments are made about clinical, mycological and therapeutic aspects of this microepidemy